Reticulation within Sporobolus: recognition of two new sections, Acinifolii and Thellungia, and a new genus, Hyalolemma (Poaceae, Chloridoideae, Zoysieae, Sporobolinae) - Paul M. Peterson; Konstantin Romaschenko; Robert J. Soreng; Yolanda Herrera Arrieta (PhytoKeys)
We present a molecular DNA phylogeny utilizing four plastid regions (rps16–trnK spacer, rps16 intron, rpl32–trnL spacer, ndhA intron) and the nuclear ribosomal internal transcribed spacer (ITS) region, investigating 123 species of subtribe Sporobolinae. We also aimed to assess the generic limits of Sporobolus, characterize possible subgeneric relationships among species in the genus, and identify hypothesized reticulation events. The core Bayesian tree, based on combined and congruent plastid and ITS regions, is well resolved, and 11 sections within a monophyletic Sporobolus are strongly supported. We describe a new genus, Hyalolemma, with two species and include a key; erect two new sections within Sporobolus, S. sect. Acinifolii and S. sect. Thellungia; and make three new combinations, Hyalolemma compactum, H. somalensis, and Sporobolus collinus. The names Eragrostis collina Trin. and Sporobolus compactus Clayton are lectotypified.